Hypertensive pregnancy deaths: a three-year review at Ghana's largest referral hospitalAJOG Global Reports at a Glance - Theodore K. Boafor; Perez Sepenu, FGCS; Ama Tamatey; Promise Sefogah; Alim Swarray-Deen; Naa Akushia Sepenu; Kwadwo Asiedu; Joshua Waliu Kamal; Winfred K. Baah; Emma Lawrence; Jerry Coleman (AJOG Global Reports)
Background: Maternal mortality continues to be a significant public health challenge in sub-Saharan Africa. Even though the leading causes, such as hypertensive disorders in pregnancy and obstetric hemorrhage have remained unchanged, associated factors continue to significantly impact reduction efforts in the maternal mortality ratio. Despite efforts, Ghana's maternal mortality ratio has not significantly decreased since 2015, the end of the Millennium Development Goals (MDGs). To achieve Sustainable Development Goal (SDG) targets, it is essential to understand and focus on reducing deaths from leading causes such as hypertensive disorders of pregnancy and emerging associated factors that contribute to maternal mortality. Objective: This study aimed to examine the contributors to maternal deaths related to hypertensive disorders at Korle Bu Teaching Hospital, Accra, Ghana. Study Design: The study was a hospital-based retrospective review of 162 audited maternal deaths occurring at the Korle Bu Teaching Hospital from January 2021 to December 2023. Data was collected using a review of medical records and clinical notes of maternal deaths as well as maternal death audit reports. The direct and indirect causes of death were analyzed, with a focus on hypertensive disorders in pregnancy. Data on socio-demographic characteristics, parity, referral status, and length of hospital stay were extracted. Maternal mortality ratio and case fatality rates were calculated. Statistical analyses were conducted to compare hypertensive-related deaths with nonhypertensive maternal deaths. Results: Hypertensive disorders in pregnancy accounted for 40.7% of all audited maternal deaths, decreasing from 52.2% in 2021 to 30.5% in 2023. Women aged 30 to 34 years had the highest number of deaths, while women over 45 had the highest maternal mortality ratio (1754.4 per 100,000 live births). Case fatality rates for hypertensive disorders decreased from 2.4% in 2021 to 1.5% in 2023. Lower parity (≤2) was associated with significantly higher mortality. Most women (77.3%) who died from hypertensive disorders were referred from other facilities. Length of hospital stay varied, with a majority of 40.9% staying seven or more days before death. The top four immediate causes of hypertensive-related maternal deaths were Eclampsia (43.9%), HELLP Syndrome (22.7%), Acute Kidney Injury (12.2%) and Pulmonary edema (9.1%). Conclusion: Hypertensive disorders are a major cause of maternal mortality at Korle Bu Teaching Hospital. Despite declining case fatality rates, the burden of hypertensive-related deaths remains significant. Improved antenatal care, efficient referral systems, and better emergency obstetric care are essential to reducing maternal mortality.